The influence of seed priming with ascorbic acid and foliar nutrition with boron in some productive traits of wheat plant (Triticum aestivum L.), Abu Ghraib cultivar. - Mehidi, Thamer (University of Thi-Qar Journal of agricultural research, 2024)
An agricultural experiment was carried out in the city of Ramadi. The experiment relied on two factors: seed priming with ascorbic acid (vitamin C) at concentrations of (0, 10, 20, 40) mg.l-1, indicated by (P0, P1, P2, P3), and boron foliar nutrition (B) at concentrations of (0, 3, 5) mg.l-1 which indicated by (B0, B1 and B2) A formula for the boric acid H3BO3 (17.4% B) compound was used to spray plants. thus, number of experimental units is 36 experimental units. The experiment was carried out according to the randomized complete block design (RCBD) and with three replications. The results showed that all concentrations of seed priming with ascorbic acid and boron foliar nutrition and their interactions had a significant increase in all of the studied traits, and this effect was found to be dose-dependent. The highest significant differences were recorded at the concentration of 40 mg.l-1 of ascorbic acid and the concentration of 5 mg.l-1 of boron (14,000 spikes. Plant-1; 4.530 gm. Plant-1; 91.00 grains. Spike-1; 50.29gm) the spike number, weight of the spike, number of grains in a spike, and weight of 1000 grains respectively